2000
DOI: 10.1073/pnas.97.7.3394
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB activation induced by T cell receptor/CD28 costimulation is mediated by protein kinase C-θ

Abstract: Protein kinase C-(PKC) is a Ca 2؉ -independent member of the PKC family that is selectively expressed in skeletal muscle and T lymphocytes and plays an important role in T cell activation. However, the molecular basis for the important functions of PKC in T cells and the manner in which it becomes coupled to the T cell receptorsignaling machinery are unknown. We addressed the functional relationship between PKC and CD28 costimulation, which plays an essential role in T cell receptor-mediated IL-2 production. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

21
148
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 150 publications
(174 citation statements)
references
References 52 publications
21
148
2
Order By: Relevance
“…The possibility that the participation of CD28 in a T cell response might be crucial to the involvement of PKC is supported by previous in vitro data centrally linking it to CD28 signals (8,24,25) and data showing that PKC -deficient CD8 cells behave almost identically to CD28-deficient CD8 cells (14). In relation to our work in this study and that of Marsland et al (23) showing defective Th2-driven lung inflammation, the connection is further supported by earlier studies demonstrating that CD28/B7 interactions are also critical to similar lung responses controlled by Th2 cells (26 -28).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The possibility that the participation of CD28 in a T cell response might be crucial to the involvement of PKC is supported by previous in vitro data centrally linking it to CD28 signals (8,24,25) and data showing that PKC -deficient CD8 cells behave almost identically to CD28-deficient CD8 cells (14). In relation to our work in this study and that of Marsland et al (23) showing defective Th2-driven lung inflammation, the connection is further supported by earlier studies demonstrating that CD28/B7 interactions are also critical to similar lung responses controlled by Th2 cells (26 -28).…”
Section: Discussionsupporting
confidence: 66%
“…PKC is more strongly expressed in T cells than other cell types and is translocated to the site of contact between T cells and APCs, where it colocalizes with the TCR/CD3 complex in the central core of the immunological synapse after TCR/CD28 ligation (3)(4)(5)(6). Furthermore, studies using pharmocological inhibitors and PKC antisense RNA and overexpression studies using dominant negative and constitutively active mutant proteins have established a role for PKC in activation of AP-1 (7) and NF-B (8,9). PKC also synergizes with calcineurin to activate NFAT and IL-2 transcription (10,11), and with Vav to mediate IL-4 gene expression in response to CD28 costimulation (12).…”
mentioning
confidence: 99%
“…NF‐κB is activated through the phosphorylation of IκB‐α which promotes to release NF‐κB into nuclear and binds to the promoter sites of target genes. Several studies have shown that PKCθ, PKCζ, PKCδ and aPKC are critical for activation of NF‐κB in T cell, monocyte, macrophage, epithelial cell, endothelial cell and microglia, respectively 46, 47, 48, 49, 50, 51. The PKC inhibitor can inhibit the phosphorylation of IκB‐α and decelerate the degradation of IκB‐α 52.…”
Section: Discussionmentioning
confidence: 99%
“…The T lymphocyte-restricted serine/threonine protein kinase protein kinase C (PKC ) 2 is unique among other PKC members because it colocalizes with the TCR in the T cell immunological synapse (2)(3)(4). In cultured cell lines, PKC -mediated signal transduction has been shown to result in activation of the transcription factors, AP-1 and NF-B, in response to TCR/ CD28 costimulation, ultimately culminating in the induction of expression of genes that are essential for the proliferation and function of activated T cells (5)(6)(7)(8). The physiological functions of PKC for TCR signaling were subsequently demonstrated by two independent studies with PKC -deficient mice (9,10).…”
mentioning
confidence: 99%
“…Peripheral T cells of PKC Ϫ/Ϫ mice show reduced proliferation and IL-2 production and significant impairment in AP-1 and NF-B (9, 10) as well as NFAT (10) activation in response to TCR/CD28 stimulation. Although numerous studies have implicated the I B␣ kinase IKK complex in linking PKC to NF-B activation (5)(6)(7)(8), the pathway responsible for coupling PKC to AP-1 appears to be JNK independent (9). Recently, a study has identified the stress-related STE20/ SPS1-like, proline alanine-rich kinase, SPAK, as a substrate and target of PKC in a TCR/CD28-induced signaling pathway leading to selective activation of AP-1, but not NF-B (11).…”
mentioning
confidence: 99%